Strategi pengembangan desain interior terhadap kenyamanan pemustaka di Perpustakaan Umum Daerah Kabupaten Lima Puluh Kota - Afrina, Cut; Zulaikha, Sri Rohyanti; Delvi, Atika Fatma; Shafutri, Ayu; Refandi, Bunga Fedra; Lutfilhadi, Hafizhand; Zulfa, M. Iqbal; Safrinal S. (Daluang: Journal of Library and Information Science, 2024)
Purpose. This study examines development strategies to improve the comfort of use in the Regional Public Library of Lima Puluh Kota Regency. Library interior design is important in creating an environment that supports learning, and research, and enhances the visitor experience. Methodology. This research uses a qualitative descriptive method. Data was collected through observation, interviews, and documentation. Results and discussion. The development strategy for enhancing user comfort at the Lima Puluh Kota District Public Library includes optimizing interior design, such as functional layouts, comfortable materials, balanced lighting, stable air temperature, soothing wall colors, and flexible spaces to support learning and research activities. With a modern and user-friendly design approach, the library becomes not only a conducive learning space but also an inclusive social interaction hub. Conclusions. The importance of interior design in creating an environment that meets user needs enhances the library's appeal as a center for learning. The library can further improve its services through modern interior design, the use of digital technology, facilities that promote comfort, community-based activities, and creative spaces to establish an inclusive and interactive library.